PARTICIPATION AND RESULTS OF MUSIC SCHOOLS OF FERGANA REGION IN REPUBLIC AND INTERNATIONAL COMPETITIONS (Scientific journal of the Fergana State University, 2024)
In this article, information on the participation and analysis of the results of music schools of Fergana region in international and republican competitions before and during the period of independence is highlighted. During this research, achievements and problems in the activities of music and art schools were reflected. is to show the place. The historicity, objectivity, consistency, and comparative-logical basis of the information provided in the article were highlighted. It also performs the task of researching and making use of information on the topic, oral history information in the current archives of music schools, regional archive funds, press pages. The information of this article can be used by researchers conducting research in the fields of music culture and history of music education in the future. Also, through this article, you can get information about national and international competitions in the field of music and art.